Cystic nephroma in a 14-year-old-a rare case report - Gopal, Reshmi; Nila, Niveditha Ezhilarasan; Menon, Dhanya; C., Vimal Chander (International Journal of Research in Medical Sciences, 2022)
Cystic nephroma (CN) is an uncommon benign renal tumor with a bimodal age distribution. It often presents with non-specific presenting symptoms. In this study, we report a case of a 14-year-old female patient who presented with a painless abdominal mass, and a left renal cystic lesion was detected on CECT KUB. Left partial nephrectomy was done and a diagnosis of CN made following the histopathological examination of specimen. Owing to its non-specific clinical presentation and radiological findings, it is difficult to distinguish CN from other cystic lesions of kidney like cystic partially differentiated nephroblastoma, tubule-cystic renal cell carcinoma, cystic Wilm’s tumor etc., pre-op. This study emphasizes importance of histopathological examination in diagnosis of CN to prevent misdiagnosis and overtreatment. Although it has good prognosis, long term follow-up for local recurrence is recommended.